The Failure of Neoliberalism and the Free Market in Cryptocurrencies: A Case Study of South Korea's Role in the Crash of Terra Luna (LUNA) - Taruliasi, Ancellmus Mario (Parahyangan Center for International Studies, 2024)
ABSTRACT This study investigates the failure of implementing neoliberalism and free market principles in cryptocurrencies, focusing on South Korea's response to the collapse of LUNA. Despite the promise of decentralization and peer-to-peer transactions inherent in cryptocurrencies, the collapse of LUNA highlights the limitations of unfettered market dynamics in ensuring stability and security. Using a qualitative research approach, this study examines the case of LUNA's collapse within the framework of neoliberal and free market concepts. Drawing on secondary sources such as articles, news, and internet sites, the research sheds light on the complexities of regulating decentralized financial systems. The findings reveal that the South Korean government intervened in the cryptocurrency market following the LUNA collapse to prevent similar incidents and establish regulatory frameworks for crypto assets. This intervention underscores the need for government oversight to maintain market stability and protect investors in the face of market volatility and manipulation. Furthermore, the study discusses the broader implications of these findings for cryptocurrency regulation and neoliberal economic policies. By examining the tensions between decentralized finance and neoliberal principles, the research contributes to a deeper understanding of the evolving relationship between government intervention and market dynamics in the cryptocurrency ecosystem. In conclusion, the study highlights the importance of regulatory oversight in safeguarding the integrity of cryptocurrency markets and ensuring the long-term sustainability of decentralized financial systems. Keywords: cryptocurrency; Luna; South Korea; neoliberalism; free market